Pediatricians’ COVID-19 experiences and views on the willingness to receive COVID-19 vaccines: a cross-sectional survey in Turkey - Erdem Gönüllü; Ahmet Soysal; Serkan Atıcı; Mesut Engin; Osman Yeşilbaş; Tuba Kasap; Atiye Fedakar; Emre Bilgiç; Emine Betül Tavil; Ercan Tutak; İsmail Yıldız; Teoman Akçay; et al. (Human Vaccines & Immunotherapeutics, 2021)
Developing an effective and safe vaccine against Covid-19 will facilitate return to normal. Due to hesitation toward the vaccine, it is crucial to explore the acceptability of the COVID-19 vaccine to the public and healthcare workers. In this cross-sectional survey, we invited 2251 pediatricians and 506 (22%) of them responded survey and 424 (84%) gave either nasopharyngeal swap or antibody assay for COVID-19 and 71 (14%) of them got diagnosis of COVID-19. If the effective and safe COVID-19 vaccine was launched on market, 420 (83%) of pediatrician accepted to get vaccine shot, 422 (83%) of them recommended vaccination to their family members, 380 (75%) of them accepted to vaccine their children and 445 (85%) of them offered vaccination to their pediatric patients. Among the participated pediatricians 304 (60%) of them thought COVID-19 vaccine should be mandatory. We found that there are high COVID-19 vaccine willingness rates for pediatricians for themselves, their own children, family members and their pediatric patients. We also found that being a pediatric subspecialist, believing in achieving an effective vaccine, willingness to participate in the phase 1–2 clinical vaccine trial, willingness to get an influenza shot this season, believing a vaccine and vaccine passport should be mandatory were significant factors in accepting the vaccine. It is important to share all information about COVID-19 vaccines, especially effectiveness and safety, with the public in a clear communication and transparency. The opposite will contribute to vaccine hesitancy and anti-vaccine movement.